Marker-aided transfer of beta-carotene biosynthetic genes (Golden Rice 1) into two Philippine rice varieties (The Philippine Journal of Crop Science, 2013)
“Golden Rice” (GR), a new type of rice that accumulates beta-carotene in the endosperm, could be an additional strategy to alleviate vitamin A deficiency (VAD) in the Philippines and other countries where VAD is prevalent. Through DNA market-aided backcrossing using rice variety Cocodrie possessing Golden Rice 1 Event 309 (GR309) as donor, several introgression lines (ILs) in the background of NSIC Rc128 and PSB Rc82 were developed. Stable ILs were verified to contain the GR309 locus using an event-specific Polymerase Chain Reaction (PCR)-based marker. Recurrent parent genome (RPG) recovery was evaluated using 98 genome-wide Simple Sequence Repeat (SSR) markers for PSB Rc82 and 103 of such markers for NSIC 128. Marker analysis revealed that at least 80% of the genetic constitution of the selected ILs were similar to the recurrent parent after 2-3 backcrosses. Majority of the ILs already resembled their recurrent parent based on 32 agro-morphological traits. Among the ILs, the highest total carotenoid concentration was at 1.80 g g-1 , higher than the 1.62 g g-1 observed in the GR donor. Ultimately, nine uniform ILs (4 from PSB Rc82 and 5 from NSIC Rc128 backgrounds) that produce beta-carotene and with high phenotypic acceptability scores were selected. Results are consistent with earlier reports that the combined use of morphological and DNA markers could enhance selection efficiency due to reduction in time, cost, and resources in producing the desired breeding lines. This strategy is now being employed in developing lines with higher level of beta-carotene using Golden Rice 2 event R (GR2-R).